FACTORS INFLUENCING SELF-MANAGEMENT BEHAVIOR IN HYPERTENSIVE PATIENTS AT LHOKNGA PRIMARY HEALTH CARE - Ningsih, Rima Wirayudha; Wardiati, Wardiati; Fahdhienie, Farrah; Septiani, Riza (Fakultas Kesehatan Masyarakat, Universitas Muhammadiyah Aceh, 2024)
Background: Hypertension is one of the non-communicable diseases suffered by a large number of people worldwide. Globally, it is estimated that 1.28 billion adults suffer from hypertension. The prevalence of hypertension is increasing, especially among those aged 60 and above. Self-management is one of the strategies for managing blood pressure in elderly with hypertension. This study aims to explore the relationship between age, gender, education, marital status, knowledge, family support, and self-management behavior among hypertensive patients at Lhoknga Primary Health Care, Aceh Besar District. Method: This study used a descriptive-analytic approach with a cross-sectional design. The study population included 510 hypertensive patients at Lhoknga Primary Health Care, Aceh Besar District. A sample of 85 individuals was selected using purposive sampling. Results: The study findings indicate a relationship between family support (p=0.012) and knowledge (p=0.001) with self-management behavior among hypertensive patients. However, no significant associations were found between the level of education (p=0.560), age (p=1.000), sex (p=0.756), comorbidities (p=0.805), and marital status (p=0.258) with self-management behavior among hypertensive patients. Recommendation: The findings of this study could serve as a basis for healthcare providers at primary healthcare centers to enhance education regarding self-management for hypertensive patients and their families, thereby increasing their awareness and motivation to implement hypertension self-management.